Barium titanate as a filler for improving the dielectric property of cyanoethyl cellulose/antimony tin oxide nanocomposite films. (July 2016) - Jia, Chao; Shao, Ziqiang; Fan, Haoyu; Feng, Rui; Wang, Feijun; Wang, Wenjun; Wang, Jianquan; Zhang, Dalun; Lv, Yanyan
Abstract: CEC/ATO and CEC/BTO/ATO nanocomposite films were fabricated by introducing barium titanate (BTO) and antimony tin oxide (ATO) in cyanoethyl cellulose (CEC) via simple solution blending technique. The morphology, microstructure, thermal stability, mechanical, optical and dielectric properties of the nanocomposite films were investigated. The results indicated that CEC/BTO/ATO nanocomposite films possessed better dielectric property and mechanical property compared with CEC/ATO nanocomposite films. This could be ascribed to the homogeneous dispersion of ATO in CEC matrix due to the introduction of BTO. The nanocomposite films with only ATO nanoparticles had a certain optical transmissibility. In addition, all the nanocomposite films possessed better thermal stability than CEC polymer.